Pregnant Women’s Factor toward Motherto-Child Transmission of HIV practice - Firman Arief; Qonita Prasta A; Enggar Ayu S; Jeanny Dwi Adriyanti; Iqbal Margi S; Prihanti Gita Sekar; Irma Nur Sukmawati (Saintika Medika, 2021)
In 2005 , there are 700.000 people infected with HIV each day around the world. Among those 200.000 are children under 15 with the highest mortality rate within those under 1 year old. According to the official guideline of released by Indonesian Ministry of Health 2011, strategies to prevent vertical infection of HIV has to be done comprehensively in order to reduce the risk to a minimum. This study aim to identify the factors of pregnant women toward mother-to-child transmission (MTCT) of HIV practice. A Cross-Sectional study design with observational analytic was conducted in this study and involving 138 pregnant woman. Data analysis used Chi-Square, Kruskal Wallis,  Mann Whitney andLogistic Regression Analysis. Multivariate analysis showed age variable, education, and attitude affect the MTCT of HIV practice significantly(age p: 0.012, OR: 0.057, CI: 0.006-0.533; education p: 0.027, OR: 0.137, CI: 0.023-0.802; attitude p: 0.012, OR: 0.224, CI: 0.069-0.725). The data showed R2 31.6% that means the MTCT of HIV practice affected by age, education and attitude, meanwhile the rest (68.4%) is affected by another factors that did't identified yet in this study.